Significance of the Expression of Rho-GDP Dissociation Inhibitorβ,γin Lung Squamous Cell Carcinoma and Adenocarcinoma - 孙曼妮 李晓倩 周静怡 刘冬明 韩昱晨 (Chinese journal of cancer research, 2007)
Objective： To study the expression of Rho-GDP dissociation inhibitor β,γ （Rho-GDIβ, Rho-GDIγ） in lung squamous cell carcinoma and adenocarcinoma and its relationship with the expression of RhoC （Ras homologus oncogenes C） and clinicopathologic parameters. Methods： Western blot assay was employed for Rho-GDIβ, Rho-GDIγand RhoC in lung squamous cell carcinoma and adenocarcinoma and non-neoplastic lung tissues of 37 cases with fresh specimens. Results： The study showed that Rho-GDIβ, Rho-GDIγ and RhoC were expressed in lung cancer and non-neoplastic lung tissues, the level in lung cancer tissue was much higher than that in non-neoplastic tissues （P〈0.001）. In lung cancer, the expression of Rho-GDIβwas much higher in patients with lymph node metastasis （P=0.021）, and the expression of Rho-GDIγ was much higher in poorly differentiated tumor than in well-differentiated and moderately differentiated tumor, but both of them were not correlated with other clinicopathologic parameters. The expressions of Rho-GDIβ and Rho-GDIγ were not correlated with the expression of RhoC. Conclusion： In lung cancer, Rho-GDIβand Rho-GDIγ may play a role in the tumorigenesis, Rho-GDIβ may promote metastasis, and Rho-GDIγ may have some relationship with differentiation.